DIACYLGLYCEROL KINASE 5 regulates polar tip growth of tobacco pollen tubes. Issue 5 (10th January 2022) - Scholz, Patricia; Pejchar, Přemysl; Fernkorn, Max; Škrabálková, Eliška; Pleskot, Roman; Blersch, Katharina; Munnik, Teun; Potocký, Martin; Ischebeck, Till
Summary: Pollen tubes require a tightly regulated pectin secretion machinery to sustain the cell wall plasticity required for polar tip growth. Involved in this regulation at the apical plasma membrane are proteins and signaling molecules, including phosphoinositides and phosphatidic acid (PA). However, the contribution of diacylglycerol kinases (DGKs) is not clear. We transiently expressed tobacco DGKs in pollen tubes to identify a plasma membrane (PM)‐localized isoform, and then to study its effect on pollen tube growth, pectin secretion and lipid signaling. In order to potentially downregulate DGK5 function, we overexpressed an inactive variant. Only one of eight DGKs displayed a confined localization at the apical PM. We could demonstrate its enzymatic activity and that a kinase‐dead variant was inactive. Overexpression of either variant led to differential perturbations including misregulation of pectin secretion. One mode of regulation could be that DGK5‐formed PA regulates phosphatidylinositol 4‐phosphate 5‐kinases, as overexpression of the inactive DGK5 variant not only led to a reduction of PA but also of phosphatidylinositol 4, 5‐bisphosphate levels and suppressed related growth phenotypes. We conclude that DGK5 is an additional player of polar tip growth that regulates pectin secretion probably in a common pathway with PI4P 5‐kinases.